ANALISIS CAMPURAN ETHANOL NILAI OKTAN 92 DAN KONDUKTIFITAS TERMAL BUSI TERHADAP DAYA DAN EMISI MOTOR 110 CC: ANALYSIS OF ETHANOL MIXTURE OCTANE VALUE OF 92 AND THERMAL CONDUCTIVITY OF THE SPARK PLUG ON POWER AND MOTOR EMISSIONS 110 CC - Mohammad Firman Rachmansyah, Mohammad Firman Rachmansyah (Jurnal Teknik Mesin, 2022)
Fuel is the main component in the combustion process in the vehicle's combustion chamber. To minimize the increasing use of fossil fuels, alternative fuels are needed to replace petroleum. Bioethanol can be used as an alternative fuel to replace petroleum.Spark plug is an important component that functions as an ignition process in the combustion chamber. Spark plugs provide sparks which will trigger combustion in the combustion chamber. This study aims to determine the effect of mixing bioethanol fuel on power and exhaust emissions by comparing the thermal conductivity of standard and iridium spark plugs. This research method uses experimental methods and data analysis. The independent variables in this study were octane 92, the thermal conductivity of standard and iridium spark plugs. The engine speed control variables start from 3000 RPM, 4000 RPM, 5000 RPM, 6000 RPM and the dependent variables in this study are power and exhaust emissions. The results of this study indicate that the use of 30% bioethanol produces a power of 7.93 hp at Rpm 6000 using iridium spark plug thermal conductivity and produces very good emissions as well.